Dominantní postavení a jeho zneužití - teoretická východiska a vývoj právní úpravy - Žák, Martin (2008)
I pay attention to modernizing of Article 82 of the Treaty which in consequence of nonelasticity of recent application of Article 82 I comsider indispensable. Applying the economic approach based on effect rather than approach based on form enables more detailed analysis of certain case, moreover, enables cempetition authorities to assess posible positive effects of certain conduct.